Racial disparities in pancreatic neuroendocrine tumors survival: a SEER study. (4th October 2017) - Zhou, Huaqiang; Zhang, Yuanzhe; Wei, Xiaoyue; Yang, Kaibin; Tan, Wulin; Qiu, Zeting; Li, Si; Chen, Qinchang; Song, Yiyan; Gao, Shaowei
Abstract: Pancreatic neuroendocrine tumor (pancreatic NETs), is an important cause of cancer‐related death worldwide. No study has rigorously explored the impact of ethnicity on pancreatic NETs. We aimed to demonstrate the relationship between ethnicity and the survival of patients with pancreatic NETs. We used the SEER database to identify patients with pancreatic NETs from 2004 to 2013. Kaplan–Meier methods and Cox proportional hazard models were used to evaluate the impact of race on survival in pancreatic NETs patients. A total of 3850 patients were included: 3357 Non‐Blacks, 493 Blacks. We stratified races as "Black" and "White/Other." Blacks were more likely to be diagnosed with later stages of tumors ( P = 0.021). As for the treatment, the access to surgery seemed to be more limited in Blacks than non‐Black patients ( P = 0.012). Compared with non‐Black patients, Black patients have worse overall survival (OS) (HR = 1.17, 95% CI: 1.00–1.37, P = 0.046) and pancreatic neuroendocrine tumors specific survival (PNSS) (HR = 1.22, 95% CI: 1.01–1.48, P = 0.044). Multivariate Cox analysis identified that disease extension at the time of diagnosis and surgical status contributed to the ethnical survival disparity. Black patients whose stages at diagnosis were localized had significantly worse OS (HR = 2.09, 95% CI: 1.18–3.71, P = 0.011) and PNSS (HR = 3.79, 95% CI: 1.62–8.82, P = 0.002). As for the patients who did not receive surgery, Blacks also have a worse OS (HR = 1.18, 95% CI: 1.00–1.41, P = 0.045). The Black patients had both worse OS and PNSS compared to non‐Black patients. The restricted utilization of surgery, and the advanced disease extension at the time of diagnosis are the possible contributors to poorer survival of Blacks with pancreatic NETs. Abstract : Our work demonstrates that Blacks with pancreatic neuroendocrine tumors have poor survival than non‐Black patients. The possible contributors to this survival disparity may be later diagnosis, less access to surgery and genetic differences.